Strategy for Effective Agricultural Marketing Extension to Meet the Challenges in 21 st Century - J.P. Singh, (Journal of Agricultural Extension Management, 2025)
As agriculture and Society develops, marketing becomes more important. In subsistence agriculture a farmer will mainly be feeding himself and his neighbours. The local community's taste and requirements are well understood. As the populations of the cities increases, farmers have the added responsibility offeeding not only the rural market but also the growing distant urban markets. Even though, the share of agriculture in India's GDP has declined from over one-third to just one-fourth, the Central Statistical Organisation survey clearly envisages that the share of agricultural enterprises in terms of number and employment is on the rise